Comparative characteristics of the state of the motor function of boys and girls aged 4-5 years - S.M. Voropay; O.V. Sukachov (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
It was considered the reliability of differences in the state of motor function between boys and girls aged 4-5 years. The study was conducted on the basis of pre-school establishments of Kirovohrad involving girls (n = 212) and boys (n = 188) aged 4-5 years. It is used a set of indicators that characterize motor skills, physiological and functional capacity of children. Identified the absence of significant differences in most parameters, except flexibility, performance of boys and girls of 4 years old. In 5 years old children differences in motor function of the state of most of the indicators are significant differences, except high-speed performance abilities and functional capacity of the system. At the organization of the educational process in physical education should be differentiated pedagogical influence on sexual differences.